HUBUNGAN PENGETAHUAN IBU HAMIL TRIMESTER III TENTANG RESIKO TINGGI KEHAMILAN DENGAN PEMILIHAN TENAGA PENOLONG PERSALINAN DI PUSKESMAS REMBANG KECAMATAN REMBANG KABUPATEN PURBALINGGA TAHUN 2010 - Ciptievisia Gusti Hechawati; Maya Safitri; Hesti Istyorini (Universitas Harapan Bangsa Purwokerto, 2011)
Background: One of the most influential factors for the high maternal mortalityrate (MMR) is the attitude and behavior, supported also by the knowledge of themother towards her pregnancy, especially of high-risk pregnancies. Due to thelevel of a fairly good knowledge of a pregnant woman will entrust himself tohealth care rather than a shaman. Based on the results of a survey conducted on22 health centers in Purbalingga, for data delivery using the quack from Januaryto November 2010 at most at the health center as much as 133 maternalRembang.Objective: To determine the relationship between knowledge about third trimesterpregnant women at high risk of pregnancy by election workers birth attendants inhealth centers Rembang Rembang sub-district in 2010.Methods: This study was descriptive correlation with cross sectional approach.The sample used is purposive sampling, the sample is third trimester pregnantwomen. Samples in this study 67 respondents. The instrument used was aquestionnaire with chi-square analysis of the data.Results: From the results, the majority of pregnant women knowledge about thehigh risk of pregnancy is pretty much as 27 respondents (40.3%), select powerdelivery by health workers as much as 44 respondents (65.7%), no relation ofknowledge of pregnant women with election auxiliary power delivery with valuecount x2> x2 table (19.631> 5.991)Conclusion: There is a relation between knowledge of pregnant women withchildbirth attendants election Keywords: Knowledge, Helper Labor, Pregnancy Trimester III, High RiskPregnancy